Glyburide nanosuspension: Influence of processing and formulation parameter on solubility and in vitro dissolution behavior (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of this study was to formulate and optimize Glyburide (GB) nanosuspension which is poorly waterâ€soluble antidiabetic drug with optimization of the dissolution property and bioavailability by reducing the particle at nano size.The nanosuspension is prepared by Top down technique, i.e. high pressure homogenization. The formulation factors whichaffects particle size including concentration of surfactant while processing parameters includes homogenization pressure andhomogenization cycle. After particle size reduction, we observe that there are increases in the surface energy which requiresadequate stabilization by surfactant. In this study, practically water insoluble GB was nanoground and surfactant was employedfor their stabilizing effect. Inâ€vitro dissolution study revealed that increase in release rate of GB from nanoparticles (NPS) ascompare to pure raw GB. Field Emission Scanning Electron Microscope (FEâ€SEM) study showed the spherical morphologyof NPS. Particles size distribution, zeta potential, and crystal form of the formulated nanosuspension were studied by usingparticle size analyzer and Xâ€ray powder diffraction. The result showed that the drug dissolution rate in nanosuspensionformulation is depending upon crystal form, solubility, preparation procedure, and stabilizer employed.Key words: Bioavailability, Glyburide, high pressure homogenization, lyophilization, nanosuspension